Penguatan Literasi Numerasi dan Huruf Hijaiyah melalui Program Pembelajaran Interaktif Berbasis Permainan pada Siswa SDI Khazanah Kebajikan - Septiarini, Tri Wijayanti; Pariyanti, Eka; Naili , Siti Umamah; Hidayat, Wahyu; Mahira, Putri (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve the numeracy literacy skills and understanding of Hijaiyah letters among students at SDI Khazanah Kebajikan through an interactive and engaging learning approach. The program was implemented in three stages: a pre-test, interactive training sessions, and a post-test, involving 44 elementary school students in a variety of group-based educational games. The data were analyzed using descriptive quantitative analysis. The results demonstrated an improvement in students' average scores, increasing from 44.1 in the pre-test to 52.7 in the post-test. In addition to enhanced numeracy literacy, the students showed improved ability to recognize Hijaiyah letters and Arabic diacritical marks, as well as greater concentration, confidence, and willingness to participate in learning activities. The program also fostered positive character traits, including teamwork, honesty, and healthy competitive spirit. Overall, the training had a positive impact on improving elementary school students' numeracy literacy and foundational Arabic literacy through the implementation of interactive, game-based learning that was both engaging and meaningful.